2018
DOI: 10.19082/6672
|View full text |Cite
|
Sign up to set email alerts
|

Medical uses of Carthamus tinctorius L. (Safflower): a comprehensive review from Traditional Medicine to Modern Medicine

Abstract: BackgroundCarthamus tinctorius L., known as Kafesheh (Persian) and safflower (English) is vastly utilized in Traditional Medicine for various medical conditions, namely dysmenorrhea, amenorrhea, postpartum abdominal pain and mass, trauma and pain of joints. It is largely used for flavoring and coloring purposes among the local population. Recent reviews have addressed the uses of the plant in various ethnomedical systems.ObjectiveThis review was an update to provide a summary on the botanical features, uses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
68
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(73 citation statements)
references
References 23 publications
1
68
0
4
Order By: Relevance
“…The medicinal properties of safflower have been recently reviewed [2,3]. Among mechanisms potentially involved in the protective roles, both anti-inflammatory and antioxidative roles have been proposed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The medicinal properties of safflower have been recently reviewed [2,3]. Among mechanisms potentially involved in the protective roles, both anti-inflammatory and antioxidative roles have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated healthy promoting properties of seed of Carthamus tinctorius L. (safflower), a traditional herbal medicine used across Asia [1][2][3][4]. Carthamus tinctorius L. seeds are known as a source of α-linoleic acid and have been used to obtain cooking oil in Europe [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many chemical compounds in alcuremon, and the main biologically active components of these plants are polyphenols, terpenes, anthocyanins, flavonoids, alkaloids, tannin, glycosides etc. 19,20,21,22,23,24,25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Alcuremon contains extract of Gentiana barbata Froel., Carthamus tinctorius L., Terminalia chebula Retz, and Rosa acicularis Lindl., these are composed of many chemical compounds, including xanthones, polyphenols, flavonoids, secoiridoids, rutin, tannins, antioxidant and others. These biologically active compounds had a wide range of pharmacological activities including antioxidant, anticancerogenic, antimutagenic, hepatoprotective, cytoprotective, cardioprotective, neuroprotective, antiviral, antiinflammatory and wound healing [19][20][21][22][23][24][25][26] . D Diosmetin is a flavonoid of the alcuremon and, it barely activates TrkB, like brain-derived neurotrophic factor (BDNF), also suppresses caspase-3 activation in neurons weakly and nonselective 27 .…”
mentioning
confidence: 99%